Amorphous indium zinc oxide film and preparation method thereof

By controlling the mass ratio of sputtering power and indium zinc oxide, and depositing indium zinc oxide films under a specific atmosphere, the problem of insufficient electrical performance of amorphous indium zinc oxide films in the prior art is solved, high carrier concentration and mobility are achieved, and photoelectric performance is improved.

CN119592912AInactive Publication Date: 2025-03-11FIRST RARE MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411753765.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to provide an amorphous indium zinc oxide film with good electrical properties.

Method used

By controlling the sputtering power during the preparation of indium zinc oxide and the mass ratio between indium oxide and zinc oxide, the indium zinc oxide target is deposited on the substrate surface under an atmosphere of inert gas and oxidizing gas to obtain an amorphous indium zinc oxide thin film.

Benefits of technology

Good electrical properties of amorphous indium zinc oxide films are achieved, including high carrier concentration and excellent carrier mobility, while improving the photoelectric properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165672220000071
    Figure BDA0005165672220000071
Patent Text Reader

Abstract

The invention belongs to the technical field of production of electricity-permeable films, and discloses an amorphous indium zinc oxide film, which is obtained by depositing an indium zinc oxide target material on the surface of a substrate under the atmosphere of inert gas and oxidizing gas by using the power of 950-1100W, and the mass ratio of indium oxide to zinc oxide in the indium zinc oxide target material is (95-99.5): (0.5-5). Through the design, the thin film has good electrical properties, and due to the fact that the indium zinc oxide thin film is in an amorphous state, the defects between band gaps caused by lattice mismatch are effectively reduced, so that the photoelectric property of the material is obviously improved, and in addition, the invention further discloses a preparation method of the amorphous indium zinc oxide thin film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrically transparent film production, and in particular to an amorphous indium zinc oxide film and a preparation method thereof. Background Art

[0002] The crystal of ZnO has wurtzite, zinc blende and NaCl structures, and its optical bandgap is 3.2eV. The most stable structure in nature is the wurtzite structure. Undoped ZnO is a II-VI semiconductor with a polycrystalline hexagonal wurtzite structure. It can be an n-type semiconductor due to the presence of intrinsic defects such as oxygen vacancies and interstitial Zn. Because the ZnO thin film system has significant advantages such as low production cost, non-toxicity, simple process control, and electrical and optical properties comparable to ITO. Traditional indium tin oxide (ITO) films show crystalline characteristics as the deposition energy increases, and crystalline ITO films can only be etched by strong acids. Therefore, it is necessary to develop a method for preparing amorphous transparent conductive films with similar optoelectronic properties.

[0003] Chinese patent application 201710051380.5 discloses a flexible composite transparent conductive film and a preparation method thereof, including a substrate and a metal oxide film, an intermediate layer film, and a metal nanowire film sequentially disposed on the substrate, wherein the intermediate layer film is a film having a greater bending resistance and conductivity than ITO. This solution adds a metal layer that makes an outstanding contribution to conductivity, effectively reduces the square resistance value of the transparent conductive film, and the metal layer also has better bending resistance than the ITO layer. At the same time, the silver nanowire film on the top layer acts as a bending protection layer. Compared with the metal oxide / metal / metal oxide composite structure transparent conductive film with relatively superior comprehensive optoelectronic performance, this solution has better bending resistance;

[0004] Further observation of the description of the scheme shows that the metal oxide film in the scheme is specifically an ITO film, an AZO film, an IZO film or an IGZO film. At the same time, the scheme also records that the metal oxide film is obtained by magnetron sputtering in a mixed atmosphere of oxygen and argon, and the sputtering power is 30 to 200 W; and the scheme does not indicate whether the metal oxide film is crystalline or amorphous.

[0005] Chinese patent application 202310078445.0 discloses a method for preparing a transparent conductive film on an organic glass substrate, wherein the organic glass substrate, the bottom protective coating and the surface protective coating are each subjected to infrared radiation treatment to be cured and aged, thereby avoiding the problem of poor interface bonding caused by the difference in thermal expansion coefficients of each layer structure during the coating curing process using a blast oven in the prior art, improving the aging resistance of the transparent conductive film on the organic glass substrate, thereby improving the stability of the transparent conductive film on the organic glass substrate, and solving the problem of easy cracking or falling off of the coating and the film layer in harsh environments such as acidic salt spray, wind and sand, extreme heat and cold;

[0006] However, the description of the solution shows that "by subjecting the conductive film layer and the transition layer to infrared radiation treatment, the conductive film layer in an amorphous state is successfully transformed into a crystalline state, thereby improving the optical and electrical properties of the conductive film layer, and causing no damage to the organic glass substrate, the bottom protective coating and the top protective coating";

[0007] It can be seen that the purpose of this scheme is to transform the amorphous film into a crystalline film through infrared radiation, and although the scheme mentions that the amorphous film is obtained by magnetron sputtering, the scheme does not clearly disclose the relevant processes and parameters of magnetron sputtering.

[0008] The problem that this solution needs to solve is: how to provide an amorphous indium zinc oxide film with good electrical properties. Summary of the invention

[0009] The purpose of the present application is to provide an amorphous indium zinc oxide film, and the present application controls the sputtering power during the preparation process of indium zinc oxide and the mass ratio between indium oxide and zinc oxide so that the amorphous indium zinc oxide film exhibits a relatively good carrier concentration and excellent carrier mobility, thereby making the film have good electrical properties.

[0010] To achieve the above-mentioned purpose, the present application discloses an amorphous indium zinc oxide film, wherein the amorphous indium zinc oxide film is obtained by depositing an indium zinc oxide target onto a substrate surface using a power of 950 to 1100 W in an atmosphere of an inert gas and an oxidizing gas;

[0011] And the mass ratio of indium oxide to zinc oxide in the indium zinc oxide target is 95-99.5:0.5-5.

[0012] Preferably, the atmosphere of the inert gas and the oxidizing gas is specifically an atmosphere of a mixed gas of argon and oxygen, and in the mixed gas, the volume ratio of argon to oxygen is 80-99:1-20.

[0013] Preferably, in the mixed gas, the volume ratio of argon to oxygen is 85-95:5-15.

[0014] In addition, the present application also discloses a method for preparing the above-mentioned amorphous indium zinc oxide thin film, comprising the following steps:

[0015] Step 1: placing the indium zinc oxide target and substrate at a preset position in the sputtering chamber;

[0016] Step 2: The sputtering chamber is adjusted to negative pressure, and then an inert gas and an oxidizing gas are introduced;

[0017] Step 3: Turn on the power supply and deposit the indium zinc oxide target onto the substrate surface at a power of 950 to 1100 W to obtain an amorphous indium zinc oxide film.

[0018] Preferably, in step 1, the distance between the indium zinc oxide target and the substrate is 45-100 mm.

[0019] Preferably, step 2 specifically includes the following sub-steps:

[0020] Step A1: Adjust the pressure in the sputtering chamber to 5.2×10 -6 ~7.7×10 -6 torr;

[0021] Step A2: A mixed gas of argon and oxygen is introduced into the sputtering chamber and the pressure in the sputtering chamber is increased to 2.5×10 -3 ~5.2×10 -3 torr, and the volume ratio of argon to oxygen in the mixed gas of argon and oxygen is 85-95:5-15.

[0022] Preferably, step 3 specifically includes: turning on the power supply, depositing the indium zinc oxide target onto the substrate surface at a power of 950 to 1100 W for a deposition time of 28 to 54 s, and then annealing to obtain an amorphous indium zinc oxide film.

[0023] Preferably, the annealing temperature is 200-500° C. and the annealing time is 30-60 min.

[0024] The beneficial effects of this application are:

[0025] The amorphous indium zinc oxide film provided by the present application controls the sputtering power and the mass ratio between indium oxide and zinc oxide during the film preparation process so that the indium zinc oxide film in an amorphous state exhibits a relatively good carrier concentration and excellent carrier mobility, thereby making the film have good electrical properties. In addition, since the indium zinc oxide film is in an amorphous state, the defects between the band gaps introduced by lattice mismatch are effectively reduced, thereby significantly improving the photoelectric properties of the material. DETAILED DESCRIPTION

[0026] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. In the description of the present invention, it should be noted that, if no specific conditions are specified in the embodiments, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0027] Example 1

[0028] Step 1: placing an indium zinc oxide target and a substrate at a preset position in a sputtering chamber, with the distance between the indium zinc oxide target and the substrate being 80 mm, and the mass ratio of indium oxide to zinc oxide in the indium zinc oxide target being 98:2;

[0029] Step 2:

[0030] Step A1: Adjust the pressure in the sputtering chamber to 6.5×10 -6 torr;

[0031] Step A2: A mixed gas of argon and oxygen is introduced into the sputtering chamber and the pressure in the sputtering chamber is increased to 4.0×10 -3 torr, and the volume ratio of argon to oxygen in the mixed gas of argon and oxygen is 90:10;

[0032] Step 3: Turn on the power supply and deposit the indium zinc oxide target onto the substrate surface at a power of 1000 W for 40 seconds, followed by annealing at a temperature of 350° C. for 50 minutes to obtain an amorphous indium zinc oxide film.

[0033] Example 2

[0034] Step 1: placing an indium zinc oxide target and a substrate at a preset position in a sputtering chamber, with the distance between the indium zinc oxide target and the substrate being 45 mm, and the mass ratio of indium oxide to zinc oxide in the indium zinc oxide target being 95:5;

[0035] Step 2:

[0036] Step A1: Adjust the pressure in the sputtering chamber to 5.2×10 -6 torr;

[0037] Step A2: Introduce a mixed gas of argon and oxygen into the sputtering chamber and increase the pressure in the sputtering chamber to 2.5×10 -3 torr, and the volume ratio of argon to oxygen in the mixed gas of argon and oxygen is 85:15;

[0038] Step 3: Turn on the power supply and deposit the indium zinc oxide target onto the substrate surface at a power of 950 W for 54 seconds, followed by annealing at a temperature of 200°C for 60 minutes to obtain an amorphous indium zinc oxide film.

[0039] Example 3

[0040] Step 1: placing an indium zinc oxide target and a substrate at a preset position in a sputtering chamber, with the distance between the indium zinc oxide target and the substrate being 100 mm, and the mass ratio of indium oxide to zinc oxide in the indium zinc oxide target being 99.5:0.5;

[0041] Step 2:

[0042] Step A1: Adjust the pressure in the sputtering chamber to 7.7×10 -6 torr;

[0043] Step A2: A mixed gas of argon and oxygen is introduced into the sputtering chamber and the pressure in the sputtering chamber is increased to 5.2×10 -3 torr, and the volume ratio of argon to oxygen in the mixed gas of argon and oxygen is 95:5;

[0044] Step 3: Turn on the power supply and deposit the indium zinc oxide target onto the substrate surface at a power of 1100 W for 28 seconds, followed by annealing at a temperature of 500° C. for 30 minutes to obtain an amorphous indium zinc oxide film.

[0045] Example 4

[0046] The method is basically the same as Example 1, except that the mass ratio of indium oxide to zinc oxide is 98:2, and step A2 specifically comprises: introducing a mixed gas of argon and oxygen into the sputtering chamber and increasing the gas pressure in the sputtering chamber to 4.0×10 -3 torr, and the volume ratio of argon to oxygen in the mixed gas of argon and oxygen is 85:15.

[0047] Example 5

[0048] The method is basically the same as Example 1, except that the mass ratio of indium oxide to zinc oxide is 98:2, and step A2 specifically comprises: introducing a mixed gas of argon and oxygen into the sputtering chamber and increasing the gas pressure in the sputtering chamber to 4.0×10 -3 torr, and the volume ratio of argon to oxygen in the mixed gas of argon and oxygen is 95:5.

[0049] Comparative Example 1

[0050] Step 1: placing an indium oxide cerium target and a substrate at a preset position in a sputtering chamber, with the distance between the indium oxide cerium target and the substrate being 80 mm, and the mass ratio of indium oxide to cerium oxide in the indium oxide cerium target being 98:2;

[0051] Step 2:

[0052] Step A1: Adjust the pressure in the sputtering chamber to 6.5×10 -6 torr;

[0053] Step A2: A mixed gas of argon and oxygen is introduced into the sputtering chamber and the pressure in the sputtering chamber is increased to 4.0×10 -3 torr, and the volume ratio of argon to oxygen in the mixed gas of argon and oxygen is 90:10;

[0054] Step 3: Turn on the power supply and deposit the indium cerium oxide target onto the substrate surface at a power of 1000 W for 40 seconds, and then anneal at a temperature of 350° C. for 50 minutes to obtain an amorphous indium cerium oxide film.

[0055] Comparative Example 2

[0056] The method is basically the same as Example 1, except that the mass ratio of indium oxide to zinc oxide is 90:10.

[0057] Comparative Example 3

[0058] The method is basically the same as Example 1, except that the mass ratio of indium oxide to zinc oxide is 99.9:0.1.

[0059] Comparative Example 4

[0060] It is basically the same as Example 1, except that in step 3, the sputtering power is 850W.

[0061] Comparative Example 5

[0062] It is basically the same as Example 1, except that in step 3, the sputtering power is 1400W.

[0063] Performance Testing:

[0064] Electrical performance test: Use a Hall effect instrument to test, use standard samples to calibrate and verify the equipment, and test the sample after the test data reaches the standard sample qualification;

[0065] Optical performance test: Use UV-visible light photometer to test and use plain glass to calibrate and verify the equipment. The specific test results are shown in Table 1:

[0066] Table 1

[0067]

[0068] Result analysis:

[0069] 1. It can be seen from Examples 1-3 that when some parameters of the preparation process of the amorphous indium zinc oxide thin film are changed, the photoelectric properties of Examples 1-3 fluctuate to a certain extent, but the fluctuation range is relatively small;

[0070] 2. It can be seen from Example 1 and Example 4-5 that when the parameters of Examples 1, 4, and 5 are all the same except for the volume ratio of argon to oxygen in the mixed gas, Examples 1, 4, and 5 show a relatively high performance gap. It can be seen from Table 1 that the mobility of Examples 4 and 5 has a significant downward trend relative to Example 1, and the resistivity has been significantly improved. At the same time, the optical performance of Examples 4-5 has also had a certain downward trend relative to Example 1. It can be seen that with the change in volume of argon and oxygen, not only the defects of the film are affected, and then the mobility of the film is affected, but also the change in volume between the two (argon and oxygen) also affects the refractive ability of the film to light;

[0071] 4. It can be seen from Example 1 and Comparative Example 1 that when the indium zinc oxide target is replaced by the indium cerium oxide target, the electrical and optical properties of the target have a significant downward trend compared with Example 1. It can be seen that the film preparation method in this application is more suitable for indium zinc oxide thin films;

[0072] 5. Further observation of Example 1 and Comparative Examples 2-3 shows that when the mass ratio of indium oxide to zinc oxide is changed relatively significantly, the electrical properties of Comparative Examples 2-3 fluctuate significantly. More importantly, the optical properties of the two show a significant downward trend. It can be seen that when the mass ratio of the two is changed, the refraction or transmission ability of the film to light changes significantly, which leads to a significant decline in the optical properties of the film.

[0073] 2. It can be seen from Example 1 and Comparative Examples 4-5 that when the sputtering power during the sputtering process is changed, the photoelectric performance of Comparative Examples 4-5 shows a certain degree of downward trend relative to Example 1, and relative to the electrical performance, the optical performance of Comparative Examples 4-5 decreases more significantly. It is speculated that the optical performance of Comparative Examples 4-5 may be significantly reduced due to the excessive fluctuation of the sputtering power, which causes the structure of the film to be different from that of Example 1.

[0074] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. An amorphous indium zinc oxide thin film, characterized in that: The amorphous indium zinc oxide thin film is obtained by depositing an indium zinc oxide target material onto a substrate surface using a power of 950 to 1100 W in an atmosphere of an inert gas and an oxidizing gas; The mass ratio of indium oxide to zinc oxide in the indium zinc oxide target is 95-99.5:0.5-5.

2. The amorphous indium zinc oxide thin film according to claim 1, characterized in that: The atmosphere of the inert gas and the oxidizing gas is specifically an atmosphere of a mixed gas of argon and oxygen, in which the volume ratio of argon to oxygen is 80-99:1-20.

3. The amorphous indium zinc oxide thin film according to claim 2, characterized in that: In the mixed gas, the volume ratio of argon to oxygen is 85-95:5-15.

4. A method for preparing the amorphous indium zinc oxide thin film according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: placing the indium zinc oxide target and substrate at a preset position in the sputtering chamber; Step 2: The sputtering chamber is adjusted to negative pressure, and then an inert gas and an oxidizing gas are introduced; Step 3: Turn on the power supply and deposit the indium zinc oxide target onto the substrate surface at a power of 950 to 1100 W to obtain an amorphous indium zinc oxide film.

5. The method for preparing an amorphous indium zinc oxide thin film according to claim 4, characterized in that: In step 1, the distance between the indium zinc oxide target and the substrate is 45 to 100 mm.

6. The method for preparing an amorphous indium zinc oxide thin film according to claim 4, characterized in that: The step 2 specifically includes the following sub-steps: Step A1: Adjust the pressure in the sputtering chamber to 5.2×10 -6 ~7.7×10 -6 torr; Step A2: Introduce a mixed gas of argon and oxygen into the sputtering chamber and increase the pressure in the sputtering chamber to 2.5×10 -3 ~5.2×10 -3 torr, and the volume ratio of argon to oxygen in the mixed gas of argon and oxygen is 85-95:5-15.

7. The method for preparing an amorphous indium zinc oxide thin film according to claim 4, characterized in that: The step 3 is specifically as follows: turning on the power supply, depositing the indium zinc oxide target onto the substrate surface at a power of 950 to 1100 W for a deposition time of 28 to 54 seconds, and then annealing to obtain an amorphous indium zinc oxide film.

8. The method for preparing an amorphous indium zinc oxide thin film according to claim 7, characterized in that: The annealing temperature is 200-500° C. and the annealing time is 30-60 minutes.

Citation Information

Patent Citations

  • Flexible composite transparent conductive thin film and preparation method therefor

    CN106653160A

  • Method for preparing transparent conductive film on organic glass substrate

    CN116313287A

  • Transparent flexible heterogeneous PN junction diode and manufacturing method thereof

    CN107623044A

  • Indium zinc oxide target material and preparation method thereof

    CN116219375A